PENGUATAN TATA KELOLA DAN INOVASI UNIT USAHA BUMDESA MELALUI PENDAMPINGAN KOLABORATIF DI KOTA DENPASAR, BALI - I Gede Nandya Oktora Panasea; I Made Endra Kartika Yudha; I Made Putra Yasa; I GST A. KT. GD. Suasana; I Wayan Suartana; I Gusti Agung Diah Arishma Okayani (Universitas Mataram, 2026)
Empowering local economies through Village-Owned Enterprises (BUMDesa) has become a key strategy to promote village self-reliance. However, in many areas including Denpasar City, challenges remain in governance, human resources, and business innovation. This community service program aimed to improve institutional capacity, governance practices, and business innovation through collaborative assistance involving universities. The program began with coordination with local government agencies, followed by training for 250 BUMDesa, selection of 50 potential BUMDesa, and intensive assistance for 12 BUMDesa in Denpasar City. Methods included needs assessment, thematic workshops, and problem-based technical mentoring. The results show improvements in financial reporting, business planning, and local-based innovations such as waste management, tourism services, and trade. Strong support from village leaders and active community participation were critical success factors. This program confirms that a collaborative approach among village governments, academics, and communities can effectively strengthen the sustainability of BUMDesa.